1985
DOI: 10.2135/cropsci1985.0011183x002500010032x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Correlations in a Modified Endosperm Texture Opaque‐2 Maize Population1

Abstract: To better understand the relationship between endosperm texture, protein quality, and other seed traits in modified endosperm (vitreous) opaque‐2 maize (Zea mays L.), estimates of additive and dominance variance, heritability, and genetic correlations were obtained for a population designated Disease Oil modified opaque‐2. Sixty S1 families were grown in 1977. In 1980, 240 S2 families (four from each S1 family) were evaluated. Families were measured for percent and degree of endosperm modification, 100 kernel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The QPM inbred lines used in this study were developed from conversion of a variety of mid-altitude normal endosperm inbred lines and OPVs to QPM and this explained the observed large genetic variability for various traits. This result is consistent with reports of genetic variability in tropical and temperate QPM germplasm (Spaner et al 1992;Vasal et al 1993a;Pixley and Bjarnason 1993;Bhatnagar et al 2004;Musila et al 2010;BaduApraku and Lum 2010;Badu-Apraku et al 2016) and in opaque-2 types (Motto et al 1978;Wessel-Beaver et al 1985).…”
Section: Discussionsupporting
confidence: 93%
“…The QPM inbred lines used in this study were developed from conversion of a variety of mid-altitude normal endosperm inbred lines and OPVs to QPM and this explained the observed large genetic variability for various traits. This result is consistent with reports of genetic variability in tropical and temperate QPM germplasm (Spaner et al 1992;Vasal et al 1993a;Pixley and Bjarnason 1993;Bhatnagar et al 2004;Musila et al 2010;BaduApraku and Lum 2010;Badu-Apraku et al 2016) and in opaque-2 types (Motto et al 1978;Wessel-Beaver et al 1985).…”
Section: Discussionsupporting
confidence: 93%
“…In modified 02 (mod-o2) kernels, modifier genes restore the endosperm to various degrees of normality. Several studies have shown that modified endosperm is quantitatively inherited (Motto, 1979;Sriwatanapongse et al, 1974;Ortega and Bates, 1983;Wessel-Beaver et al, 1985;Glover and Mertz, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Results of Wessel-Beaver et al (1985) showed a greater genetic variance among families versus within families for the traits of plant height, percent lysine, percent protein, and lysine per 100 grams of protein. All other traits showed greater genetic variances for the within families component.…”
mentioning
confidence: 96%
“…In a more recent study, Wessel-Beaver et al (1985) estimated the variances among and within families derived from a modified opaque-2 maize population for endosperm modification, protein quality, and kernel traits. Evaluated material was obtained by selfing within 60…”
mentioning
confidence: 99%
See 1 more Smart Citation